Evaluation of blood metal levels of hockey teams after playing on synthetic turf fields - GULLU, Esin; EFDAL, Abdulsamet; GULLU, Abdullah; CETIN, Ihsan (Faculty of Medicine, Universitas Trisakti, 2023)
Background Artificial turf fields are widely used as an alternative to natural grass in many areas such as parks, playgrounds, and playing fields. In this study, we aimed to evaluate the toxicological effects of the chemicals contained in the fields consisting of artificial turf and crumb rubber on the blood metal levels in field hockey players. MethodsA cross-sectional study was conducted involving 28 apparently healthy men aged 20-25 years who participated in this study voluntarily. They consisted of 17 field hockey athletes [athlete group (AG)] and 11 sedentary males [control group (CG)]. Before and after the 7-day tournament, blood samples were taken from AG and CG to measure mercury, arsenic, aluminum, lead, zinc, magnesium and iron levels. An independent t-test was used to analyze the data. ResultsIn comparisons between CG and AG, the magnesium level of AG before the tournament was higher, while the iron and mercury levels were significantly lower (p<0.05). In intragroup comparisons, a significant increase was observed in the post-tournament magnesium and iron variables in the AG group (p<0.05). In post-tournament intergroup comparisons, increases in the Mg and decreases in the Hg variables of AG were significant (p<0.05). ConclusionIt is thought that as a result of the tournament on fields with synthetic grass surfaces, the male field hockey players in the 20-25 age group were toxicologically not affected by the harmful heavy metals present in these fields, because the Hg, As, Pb, Zn, Al, Fe, and Mg levels are within the international reference ranges.